2016
DOI: 10.1038/srep21318
|View full text |Cite
|
Sign up to set email alerts
|

Reduced brain activation in violent adolescents during response inhibition

Abstract: Deficits in inhibitory control have been linked to aggression and violent behaviour. This study aimed to observe whether violent adolescents show different brain activation patterns during response inhibition and to ascertain the roles these brain regions play. A self-report method and modified overt aggression scale (MOAS) were used to evaluate violent behaviour. Functional magnetic resonance imaging was performed in 22 violent adolescents and 17 matched healthy subjects aged 12 to 18 years. While scanning, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…Although the hippocampus is not typically linked to response inhibition and its role has mainly been demonstrated during contextual fear inhibition (6, 7, 9), we have previously demonstrated a relationship between hippocampal activation during response inhibition and PTSD symptoms (18, 19). Hippocampal functioning in Go/NoGo tasks has also been demonstrated in other studies: less hippocampal activation was shown in heavy drinkers compared to light drinkers (44), in violent adolescents (45), and in cannabis-using ADHD patients (46) relative to controls. Similarly, hippocampal activation during Go/NoGo was found to increase post-treatment in adolescents with bipolar disorder (47).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Although the hippocampus is not typically linked to response inhibition and its role has mainly been demonstrated during contextual fear inhibition (6, 7, 9), we have previously demonstrated a relationship between hippocampal activation during response inhibition and PTSD symptoms (18, 19). Hippocampal functioning in Go/NoGo tasks has also been demonstrated in other studies: less hippocampal activation was shown in heavy drinkers compared to light drinkers (44), in violent adolescents (45), and in cannabis-using ADHD patients (46) relative to controls. Similarly, hippocampal activation during Go/NoGo was found to increase post-treatment in adolescents with bipolar disorder (47).…”
Section: Discussionsupporting
confidence: 74%
“…Hippocampal lesions in rats resulted in impulsive choice, reflected in a preference for an immediate small reward over a delayed, larger reward (60). Impulsive choice may explain reduced inhibition-related hippocampal activation seen in heavy drinkers (44), violent adolescents (45), and ADHD patients (46). Impulsivity has also been associated with the development of PTSD in both military (61) and civilian populations (62).…”
Section: Discussionmentioning
confidence: 99%
“…These results are also consistent with the findings of other studies in adolescents. For instance, it has been shown that a group of violent adolescents made more errors on a Go/no-go task than a control group ( Qiao et al (2016) . Although relatively few studies have evaluated the particular relation between parental education and aggression in children ( Letourneau et al, 2013 ), some studies with an adolescent sample have shown how higher levels of parental education are related to fewer instances of aggressive behavior ( Nocentini et al, 2010 ; Véronneau et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the prevalence and undesirable consequences of aggression, looking for protective factors that prevent or reduce its progress during childhood is an essential goal. There is already some evidence to suggest that certain variables could be important in reducing these behaviors, such as parental education and the capacity for inhibitory control, both of which have been linked to aggressive behaviors, particularly in adolescents ( Raaijmakers et al, 2008 ; Nocentini et al, 2010 ; Vuontela et al, 2013 ; Véronneau et al, 2014 ; Qiao et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation